Legal Protection for Auction Winners Executing Mortgage Rights Who Cannot Control The Auction Object - Rahmadina, Farah Dania; Shallman, Shallman (TABELLIUS: Journal of Law, 2024)
This research aims toto know and analyze legal protection for auction winners of mortgage execution who cannot control the auction object and to know and analyze the obstacles to auction winners of mortgage execution who cannot control the auction object. This study uses a statutory approach (Statuta Approach), the type of research used in this study is normative legal research, the type of data in this study is secondary data, the data collection method in this study is library research, and the data analysis used is prescriptive analysis. The results of the study indicate that legal protection for buyers or auction winners has not been able to provide legal certainty for buyers or auction winners. Both the seller and the State Asset and Auction Service Office (KPKNL) do not have responsibility and liability for control of the auction object. Repressive legal protection provided by the government to auction winners who cannot control the auction object is to request assistance for vacating directly to the Head of the District Court. As is known, the process from the application for vacating to the execution of vacating does not have a certain time and often takes a long time so that the buyer does not obtain legal certainty to obtain his rights, there are also various obstacles in the process of implementing the mortgage execution auction. These obstacles consist of legal obstacles and non-legal obstacles. Legal obstacles include the existence of unclear or conflicting laws and regulations, while non-legal obstacles relate to technicalities and the execution process in court. The existence of these obstacles causes the lack of legal certainty for the auction winner to enjoy the object of his property rights.